Biodegradable stents for caustic esophageal strictures: a new therapeutic approach. Issue 3 (13th September 2012) - Karakan, T.; Utku, O. G.; Dorukoz, O.; Sen, I.; Colak, B.; Erdal, H.; Karatay, E.; Tahtaci, M.; Cengiz, M.
Summary The treatment of caustic esophageal strictures is a challenging topic. Although traditional therapies have limited efficacy, most of these patients eventually require surgery. Biodegradable (BD) stents are newly designed stents for benign conditions. This is a retrospective case series of seven patients with caustic esophageal stricture. BD esophageal stents were inserted for palliation of dysphagia. The position of the stent was checked at 1, 4, 8, 12 16, 20, and 24 weeks and at the end of follow‐up period. The follow‐up period was 60 ± 23 (36–102) weeks. Complete dissolution of the stent occurred at 16 ± 4 (12–20) weeks. Three patients had partial/complete relief of dysphagia. The remaining four patients experienced tissue hyperplasia at the edges of the stent and required serial dilations. At the end of follow‐up, all patients had partial or complete relief of dysphagia. Although BD stents have some efficiency, tissue hyperplasia is the main limiting factor. Further randomized trials are needed to determine efficiency of BD stents for caustic damage.